Durability and corrosion studies in prestressed concrete made with blended cement - Arora, V V; Singh, Brijesh; Patel, Vikas (Journal of Asian Concrete Federation, 2019)
Corrosion of steel embedded in reinforced concrete and prestressed concrete structures is a global problem. In general, corrosion in reinforced concrete shows some symptoms of failure before any catastrophic failure while, in prestressed concrete, sudden catastrophic failure may occur without any symptoms of failure. This could be due to the conjoint action of stress and corrosion on prestressing wires embedded in concrete. This paper presents the durability and corrosion study on two different grades M40 and M60 concretes and three different brands of cement i.e. one Ordinary Portland Cement (OPC) and two Portland Pozzolana Cement (PPC) (PPCs with fly ash content of 25 percent). The prestressed concrete beams in coastal environment were subjected to alternate wetting and drying (3% NaCl solution) and test parameters were measured for one year. Based on the durability and corrosion studies done, it can be concluded that PPC is more durable than OPC in coastal/aggressive environment owing to high resistance to chloride ion penetration in PPC. However, the carbonation test carried out on the prestressed concrete beams after six years indicated that the carbonation depth in PPC is higher than OPC. Therefore, in non-coastal region additional care with respect to concrete grade and concrete cover should be taken in design consideration.